UNIMAS Bus Ticketing System - Andy, Yee Wee Chieh (Universiti Malaysia Sarawak (UNIMAS), 2005)
Online ticketing is becoming very famous as it brings convenience to the user. Demand towards online ticketing is becoming higher and higher because it gives many advantages to the user. Online ticket has proven that it is fast and easy to use and at the same time able to reduce the ticket fare because the drop in the management cost. From time to time, many web site exist in the web to provide such facility thus increase the user power of choose. As there are many online ticket sites in the web right now, user tends to look for usability online ticket site. UNIMAS Bus Ticketing System is a web site that provides online bus ticket booking and purchasing system to the end user. The main aim of the system is to provide a useable site to the user and at the same time provides another alternative to the user to purchase a ticket. The target user is concentrated on the university student. The system also provide convenience to the student so that the student does not have to wasting their time going and queuing at the counter sales ticket in order to buy a ticket. UNIMAS Bus Ticketing System site is made by taking into consideration the usability guideline. This is to ensure that the site gives the user the freedom when they navigate the site. The site is implemented by using combination of Active Server Page (ASP), Java Script, VB Script and Hyper Text Markup Language (HTML). The database of the website is created and managed by using Microsoft Acces